2011
DOI: 10.1080/15374416.2011.546050
|View full text |Cite
|
Sign up to set email alerts
|

Treatment Outcomes and Mediators of Parent Management Training: A One-Year Follow-Up of Children with Conduct Problems

Abstract: This effectiveness study presents the results of a 1-year follow-up of a randomized controlled trial of Parent Management Training. Families of 112 Norwegian girls and boys with clinic-level conduct problems participated, and 75 (67%) families were retained at follow-up. Children ranged in age from 4 to 12 at intake (M = 8.44). Families randomized to the control group received an active treatment alternative as would be normally offered by participating agencies. Multi-informant, multisetting outcome measures … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
47
0
5

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 77 publications
(58 citation statements)
references
References 43 publications
6
47
0
5
Order By: Relevance
“…The current study, moreover, extends findings from the smaller clinical trials by reporting maintenance of treatment gains for ODD and improvements in certain functional domains (e.g., relationship with playmates or peers, overall severity of child problems and need for treatment) at 6-month follow-up. Such findings are also consistent with the maintenance of treatment effects from post-test to follow-up assessment periods for similar parent management training programs tested within routine clinic settings (e.g., Axberg and Broberg 2012; Behan et al 2001; Costin and Chambers 2007; Gardner et al 2006; Hagen et al, 2011; Hautmann et al 2009; Kleve et al 2010; Kling et al 2010; Kjobli and Ogden 2013; Larsson et al 2009; Ogden and Hagen 2008). …”
Section: Discussionsupporting
confidence: 75%
See 3 more Smart Citations
“…The current study, moreover, extends findings from the smaller clinical trials by reporting maintenance of treatment gains for ODD and improvements in certain functional domains (e.g., relationship with playmates or peers, overall severity of child problems and need for treatment) at 6-month follow-up. Such findings are also consistent with the maintenance of treatment effects from post-test to follow-up assessment periods for similar parent management training programs tested within routine clinic settings (e.g., Axberg and Broberg 2012; Behan et al 2001; Costin and Chambers 2007; Gardner et al 2006; Hagen et al, 2011; Hautmann et al 2009; Kleve et al 2010; Kling et al 2010; Kjobli and Ogden 2013; Larsson et al 2009; Ogden and Hagen 2008). …”
Section: Discussionsupporting
confidence: 75%
“…Specifically, Kjobli and Ogden (2013) found statistically significant small to medium (i.e., 0.39–0.47) effect sizes in reduction of child behavior difficulties at 6-month follow-up using ITT analyses. Hagen et al (2011) reported no significant between-group differences on analyses including 1-year follow-up measures on child behavior outcomes using ITT analyses, and only small effect sizes (i.e., 0.08–0.29) among those who actually received treatment. Effect sizes for between group analyses in the current study are also consistent with those reported (average d = 0.30) by Lee et al (2013) in their analysis of 13 effectiveness studies conducted in routine clinic settings for treating youth DBDs.…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…The intervention has been implemented statewide in Michigan and Kansas (Forgatch et al, 2013), and nationwide in Norway, Iceland, Denmark, and The Netherlands (e.g., Bekkema, Wiefferink, & Mikilajczak, 2008; Ogden, Forgatch, Askeland, Patterson, & Bullock, 2005; Ogden, Hagen, Askeland, & Christensen, 2009; Sigmarsdóttir & Björnsdóttir, 2012; Sigmarsdóttir & Guđmundsdóttir, 2012). In all these instances, fidelity is carefully monitored to prevent drift (Forgatch & DeGarmo, 2011; Sigmarsdóttir & Guđmundsdóttir, 2012), and notable improvements in child and parent outcomes have been found (Hagen, Ogden, & Bjørnebekk, 2011; Sigmarsdóttir et al, n.d.). The intervention has been culturally adapted for use with ethnic minorities in the United States (Domenech Rodríguez et al, 2011; Parra-Cardona et al, 2012) and Norway (Bjørknes, Kjøbli, Manger, & Jakobsen, 2012).…”
Section: Overview Of Pmtomentioning
confidence: 99%